Partial Replacement of EPDM by GTR in Thermoplastic Elastomers Based on PP/EPDM: Effects on Morphology and Mechanical Properties - Lima, Paulo
The formulation of recycled thermoplastic elastomeric materials (TPE) based on ground tyre rubber (GTR), generated from end of life tyres, can be an alternative strategy to deal with a type of waste responsible for increasingly environmental problems over the past decades. The incompatibility of GTR with thermoplastics places several issues on the formulation of these materials, which this study tries to overcome. An encapsulation strategy of the GTR by an elastomeric phase is proposed in this work to overcome the lack of adhesion between the materials. Ternary blends, composed of a highly flowable polypropylene homopolymer, an ethylene propylene diene monomer (EPDM) and GTR were formulated and their morphology and mechanical properties analyzed. The morphology of the blends showed interaction between the materials, revealing that the encapsulation of GTR by a rubber phase can be an adequate strategy to formulate recycled-based TPE materials, if the dimension of the GTR particles is controlled and taken into consideration. The mechanical properties revealed the replacement effect of EPDM by GTR, and its dependence on the amount of that replacement. (c) 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40160.